The Teachers’ Necessity in Developing Their Competences Through Learning Process in University - Fadhlan Saini; Maryam Lughu (IAIN Manado, 2020)
Abstract The aim of this study was to figure out the reasons about the necessity of honorer teachers to continue their study and to reveal the implication of honorer teachers’ teaching and learning process at university into their classroom. Descriptive Qualitative Method was applied through interview and documentation. In this study, the researchers synthesized the results of interview from selected Islamic honorer teachers as the primary source. The secondary source was accomplished by related articles and books or documentations of the research. The results showed that there were five reasons of the necessity such as (1). Based on the law number 14 of 2005 chapter 4 verse 8 – 13 and The Indonesian Republic Government Regulation No 49 of 2018 chapter 8, (2). To improve their teachers’ competences, (3). To raise their position to the next level such as bachelor degree (4). To get better salary, and (5). To get Educator Identity Number. Meanwhile, the implication was studied and needed for further improvement for their competences. Furthermore, the honorer teachers required to have lots knowledge, apprehend to manage the classroom, understand to communicate, cooperate and have a good relationship with students emotionally or even spiritually